Belonging and the Religiousness of Sport: The Conceptuality of 'Multiple Religious Belonging' and the Liverpool Kop - Ellis, Robert (Louvain studies, 2022)
The 'religiousness' of sport, and in particular the notion of 'belonging', is examined through the example of Liverpool FC and its relationship with its fans. The starting point is the ongoing collective response to the Hillsborough tragedy of 1989, which dramatises issues in a vivid way. The appropriateness of speaking of 'religion' at all is briefly considered, before using the conceptuality of multiple religious belonging as a lens through which to view the Liverpool phenomena. This in turn offers some conclusions both about the football case study and about the conceptuality of multiple religious belonging, its uses and limitations.